Prokrastinasi akademik pada mahasiswa yang menjalani perkuliahan daring: Bagaimana peranan efikasi diri? (SUKMA : Jurnal Penelitian Psikologi, 2021)
This research was conducted to determine the relationship between self-efficacy and academic procrastination in students undergoing online lectures. This research is included in correlational research. The population in this study were all students from various departments and were still actively studying at 17 August 1945 University Surabaya. The sampling technique used was Non Probability sampling with incidental sampling type. The collection of data sources in this study used the Self-Efficacy scale and the Academic Procrastination scale. Data analysis in this study used statistical parametric techniques, namely product moment correlation test by testing self-efficacy variables and academic procrastination variables using IBM SPSS 16.0 for windows. Based on the results of data analysis using the product moment correlation test, it can be seen that the correlation coefficient value obtained is -0.624 with a significant value of 0.000 or <0.01 is very significant, thus it can be concluded that there is a negative or very significant relationship between the self-efficacy variables. with the academic procrastination variable, in other words, the higher the level of self-efficacy, the lower the level of academic procrastination. Vice versa, the lower the level of self-efficacy, the higher the level of academic procrastination.Keywords: Self-Efficacy, Academic Procrastination, Online LearningPenelitian ini dilakukan bertujuan untuk mengetahui hubungan antara Efikasi diri dengan Prokrastinasi Akademik pada Mahasiswa yang Menjalani perkuliahan Daring. Penelitian ini termasuk dalam penelitian korelasional. Populasi dalam penelitian ini adalah seluruh mahasiswa dari berbagai jurusan dan masih aktif menempuh pelajaran di Universitas 17 Agustus 1945 Surabaya. Teknik pengambilan sampel yang digunakan adalah Non Probability sampling dengan jenis insidental sampling. Pengumpulan sumber data dalam penelitian ini menggunakan skala Efikasi Diri dan skala Prokrastinasi Akademik. Analisis data dalam penelitian ini menggunakan teknik statistic parametric yaitu uji korelasi product moment dengan menguji variabel efikasi diri dan variabel prokrastinasi akademik dengan menggunakan SPSS 16.0 IBM for windows. Berdasarkan hasil analisis data menggunakan uji korelasi product moment maka dapat diketahui bahwa nilai koefisien korelasi yang diperoleh sebesar -0,624 dengan nilai signifikan 0,000 atau <0,01 sangat signifikan, dengan demikian maka dapat ditarik kesimpulan bahwa terdapat hubungan negatif atau sangat signifikan antara variabel efikasi diri dengan variabel prokrastinasi akademik, dengan kata lain semakin tinggi tingkat efikasi diri maka akan semakin rendah tingkat prokrastinasi akademik. Begitu pula sebaliknya, semakin rendah tingkat efikasi diri maka akan semakin tinggi tingkat prokrastinasi akademik. Kata Kunci: Efikasi Diri, Prokastinasi Akademik, Kuliah Daring